2023
DOI: 10.1002/ppul.26318
|View full text |Cite
|
Sign up to set email alerts
|

Clinical change 2 years from start of elexacaftor‐tezacaftor‐ivacaftor in severe cystic fibrosis

Abstract: Rationale Limited published research is available on the impact of elexacaftor/tezacaftor/ivacaftor (ETI) beyond the initial few months postdrug initiation, especially for those who initiated therapy via individual investigational new drug application. The experiences of patients with cystic fibrosis (CF) experiencing severe lung disease were reviewed for significant improvements in clinical symptoms and quality of life. Objectives To examine clinical outcomes 2 years post‐ETI in patients with CF and advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
(49 reference statements)
3
12
0
Order By: Relevance
“…Just as in our study, they described all patients reaching clinical stability while the drug was well tolerated. 13 Inclusion criteria for both phase III trials for ELE/TEZ/IVA included ppFEV 1 above 40, so that the studied groups are not easily comparable to ours. For effects on FEV 1 , both the trial including homozygous F508del pwCF and the one including F508del/MF pwCF found a larger difference after initiation of the treatment compared to the increase in our study.…”
Section: Resultsmentioning
confidence: 87%
“…Just as in our study, they described all patients reaching clinical stability while the drug was well tolerated. 13 Inclusion criteria for both phase III trials for ELE/TEZ/IVA included ppFEV 1 above 40, so that the studied groups are not easily comparable to ours. For effects on FEV 1 , both the trial including homozygous F508del pwCF and the one including F508del/MF pwCF found a larger difference after initiation of the treatment compared to the increase in our study.…”
Section: Resultsmentioning
confidence: 87%
“…This suggests potential contribution from altered metabolism, energy balance and energy expenditure. Among those with severe lung disease, similar positive impacts have been noted in lung function, quality of life and BMI [11 ▪ ,12].…”
Section: Current Landscapementioning
confidence: 52%
“…McCoy and collaborators retrospectively assessed various clinical parameters, such as ppFEV 1 , BMI, SCC, and QoL, in a two-year post-ETI period in 18 PwCF (aged 15–49 years) with advanced lung disease [ 56 ]. Overall, ETI therapy was well-tolerated, and no participant discontinued it in the two-year follow-up period.…”
Section: Clinical Outcomes Of Eti Therapy In Case Reports Observation...mentioning
confidence: 99%
“…There were no new safety concerns, and no participant required a lung transplant over the follow-up period. Regarding efficacy, data demonstrated a sustained improvement in clinical outcomes, including lung function, nutritional status, and respiratory symptoms, which resulted in a reduction in therapy burden and, consequently, a better quality of life for PwCF [ 56 ].…”
Section: Clinical Outcomes Of Eti Therapy In Case Reports Observation...mentioning
confidence: 99%